2011
DOI: 10.3892/or.2011.1398
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular architecture of early esophageal neoplasia

Abstract: Abstract. Progress in magnifying endoscopy has allowed endoscopic atypia to be evaluated on the basis of the presence or the absence of microvascular hyperplasia in a tumor. We focused our attention on intra-epithelial papillary capillary loops (IPCLs) and studied 20 cases of esophageal neoplasia (IPCL type III, 10 cases; IPCL type IV, 10 cases) and 99 vessels (IPCL type III, 24 vessels; IPCL type IV, 75 vessels). We evaluated the histopathological findings and measured vessel caliber, distance from the baseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Subjects were retrospectively divided into the following two groups according to the type of knife used for ESD: the hook knife was used for 21 lesions from September 2006 to September 2009 (hook group), and the SB knife was used for 17 lesions from October 2009 onward (SB group). Indications for ESD included the following: (i) histological examination showing high‐grade intraepithelial neoplasms or squamous cell carcinoma; (ii) no lymph node involvement or distant metastasis observed on computed tomography (CT); (iii) no submucosal invasion observed on endosonography with through‐the‐scope endoscopic ultrasonography; and (iv) patterns of intrapapillary capillary loops observed under magnifying endoscopy (GIF‐Q240Z or GIF‐H260Z; Olympus Optical Co., Ltd, Tokyo, Japan) with narrow band imaging shown to be type IV or V1 and V2 . The lesion size was not an exclusion criterion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were retrospectively divided into the following two groups according to the type of knife used for ESD: the hook knife was used for 21 lesions from September 2006 to September 2009 (hook group), and the SB knife was used for 17 lesions from October 2009 onward (SB group). Indications for ESD included the following: (i) histological examination showing high‐grade intraepithelial neoplasms or squamous cell carcinoma; (ii) no lymph node involvement or distant metastasis observed on computed tomography (CT); (iii) no submucosal invasion observed on endosonography with through‐the‐scope endoscopic ultrasonography; and (iv) patterns of intrapapillary capillary loops observed under magnifying endoscopy (GIF‐Q240Z or GIF‐H260Z; Olympus Optical Co., Ltd, Tokyo, Japan) with narrow band imaging shown to be type IV or V1 and V2 . The lesion size was not an exclusion criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Indications for ESD included the following: (i) histological examination showing high-grade intraepithelial neoplasms or squamous cell carcinoma; (ii) no lymph node involvement or distant metastasis observed on computed tomography (CT); (iii) no submucosal invasion observed on endosonography with through-the-scope endoscopic ultrasonography; and (iv) patterns of intrapapillary capillary loops observed under magnifying endoscopy (GIF-Q240Z or GIF-H260Z; Olympus Optical Co., Ltd, Tokyo, Japan) with narrow band imaging shown to be type IV or V1 and V2. 9,10 The lesion size was not an exclusion criterion. Written informed consent was obtained from all patients before esophageal ESD.…”
Section: Methodsmentioning
confidence: 99%
“…With the assistance of a narrow band imaging (NBI) system, magnifying endoscopy enables the clear visualization of fine mucosal architecture and microvasculature [1], [2]. Inoue et al reported the significance of intra-capillary papillary loop (IPCL) change including irregular dilation and caliber changes in diagnosing esophagopharyngeal squamous cell carcinoma (SCC) [3] [4] [5]. IPCL alteration is one of the earliest changes observed in superficial SCC.…”
Section: Introductionmentioning
confidence: 99%
“…This classification simply offers information of whether the pathological confirmation should be performed by differentiating type III and IV. Recently, Kaga et al [12] evaluated the detailed vascular structure pathologically and concluded that differences in vessels between IPCL type III and IV are highlighted by two factors: increased vessel caliber and prolongation of IPCLs toward the surface.…”
Section: Ipcl Classificationmentioning
confidence: 99%